Adverse Effects of Childhood Emotional Maltreatment on Child Behavioral Outcomes. Issue 2 (7th February 2016) - Meller, Suzanne; Kuperman, Kelsey L.; McCullough, Courtney; Shaffer, Anne
ABSTRACT: This study used a diverse community sample to test a moderated mediation model, investigating maternal depressive symptoms as a mediator of the relations between maternal emotional maltreatment and child behavior problems; we further tested the moderating effects of observed maternal hostility on these relations. Participants included 64 mother–child dyads (8–11 years old; 59.4% female), in which mothers completed self- and child-report measures and dyads completed a conflict resolution task. Results of a moderated mediation analysis (PROCESS; Hayes, 2013) indicated that the maternal history of emotional maltreatment was associated with increased maternal depressive symptoms, and subsequently with higher child externalizing problems. In addition, these relations were strongest at high levels of observed maternal hostility in the conflict task.